2017
DOI: 10.3389/fnins.2017.00253
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Motor Control during Three-Dimensional Movements Tracking with Position-Varying Gravity Compensation

Abstract: Active movements are important in the rehabilitation training for patients with neurological motor disorders, while weight of upper limb impedes movements due to muscles weakness. The objective of this study is to develop a position-varying gravity compensation strategy for a cable-based rehabilitation robot. The control strategy can estimate real-time gravity torque according to position feedback. Then, the performance of this control strategy was compared with the other two kinds of gravity compensation stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Step 4: The probability function ϕ m averaged all the similarities from any matrices in the time series to another and is expressed as (N , n, r) (11) where fApEn 3D is used to assess the incremental comparisons between the m-and the m + 1-dimensional space.…”
Section: ) Calculation Of Fapen 3dmentioning
confidence: 99%
See 3 more Smart Citations
“…Step 4: The probability function ϕ m averaged all the similarities from any matrices in the time series to another and is expressed as (N , n, r) (11) where fApEn 3D is used to assess the incremental comparisons between the m-and the m + 1-dimensional space.…”
Section: ) Calculation Of Fapen 3dmentioning
confidence: 99%
“…3c), which demonstrates that movements made by subjects became less smooth, and the multiple joints were less coordinated. Recent studies have revealed that increasing both the target distance [34] and movement direction [11] influences the coordinated movement response. Other studies have illustrated that to achieve necessary positions, the sensorimotor system should regulate sequential muscle control for the subsequent coordination [6], [15].…”
Section: A Effect Of the Trajectory Dimension On Sensorimotor Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The complexity of experimental designs that have been used is quite broad with target and pursuer trajectories embedded in varying dimensionalities of an original fixed coordinate system and various pursuer position generation mechanisms can be involved. These variations can range from target and pursuer trajectories being embedded in a one-dimensional space [8] to both trajectories being embedded in a three dimensional space, such as that used in robotic rehabilitation [9]. Embedding space dimensionalities for trajectories within a specific pursuit tracking task design are not necessarily uniform.…”
Section: Introductionmentioning
confidence: 99%